Antifouling paint particles: Sources, occurrence, composition and dynamics. (15th June 2018) - Soroldoni, Sanye; Castro, Ítalo Braga; Abreu, Fiamma; Duarte, Fabio Andrei; Choueri, Rodrigo Brasil; Möller, Osmar Olinto; Fillmann, Gilberto; Pinho, Grasiela Lopes Leães
Abstract: Sources, occurrence, composition and dynamics of antifouling paint particles (APPs) were assessed in Patos Lagoon estuary (PLE), Southern Brazil. Ten areas including boatyards, a marina and artisanal fishing harbors were identified in the estuarine system as potential sources of APPs. The APPs generated in these areas were highly heterogeneous considering the size, shape and composition. Based on an estimate of antifouling paint usage and amount of boats in each studied area, artisanal fishing harbors could be the main source of particles to PLE. However, relatively high amounts of APPs, which ranged from 130 to 40, 300 μg g −1, were detected in sediments collected in front of boatyards and a marina. The uneven distribution of APPs levels among the sediment samples were probably due to the presence of diffuse sources (fishing harbors) associated to "hotspots" (boatyards and marina) along the study area. Additionally, data of settling experiment indicate that size, shape and density of APPs, combined to local hydrodynamics, appears to contribute to the mobility of these residues within the estuary. In the main channel of PLE, smaller particles tend to be transported to adjacent coastal zone while particles tend to be deposited in the sediment surface of sheltered areas. Since different trace metals, and booster biocides were detected in APPs that were not correctly disposed, these particles can be considered as an important source of contamination to aquatic environments. The present data suggest that APPs represent an environmental problem for aquatic systems in Brazil, since the country lacks legislation in addition to inefficient control mechanisms. An improvement in boat maintenance processes are urgently needed to avoid this continuous release of APPs into the aquatic systems. Graphical abstract: Highlights: Removal of old antifouling paint coatings produces antifouling paint particles (APPs). Source, occurrence, composition and dynamics of APPs were assessed. APPs are direct sources of metals and booster biocides to water column and sediments. Distribution of APPs is controlled by size, shape, density and local hydrodynamics. APPs are an environment issue in ship/boat maintenance facilities.